An ecological evaluation using fisheries landings time-series data: A case study of two coastal lagoons in the Ionian sea (E. Mediterranean, Greece). (5th January 2019) - Zoulias, Theodore; Papadopoulos, Aggelos; Conides, Alexios
Abstract: Landing time series in Paleo and Avlemon lagoons (Lefkada Island, NW Greece) were analyzed for the time period 1989–2014 in order to estimate the environmental status and the fishing pressure imposed on the studied lagoon ecosystems in relation to fisheries production. In both lagoons the fishing yield and the Fishing in Balance index (FiB), showed a significant decreasing trend. In contrast, the mean trophic level index (mTL) increased with throughout the study period likely influenced by detrivorous trends and mid-level carnivorous trophic groups. The relative biomass trophic level spectra (BTLS) index analysis for the sub periods 1989–1998, 1999–2001 and 2002–2014 indicated no major shifts in the trophic structure. Meta analysis of indicators between the two target lagoons with other similar lagoon systems in Greece, based on their average physical and chemical variables, showed that Paleo lagoon is characterized by the temperature, the dissolved oxygen and ammonium concentrations while the Avlemon lagoon by the salinity values. The combination of the used indicators revealed a contracting fishery activity in both lagoons but a Gordon-Schaefer analysis, according to CPUE indicator (t/fisherman/year), showed that the Paleo lagoon is an underexploited system, while in the Avlemon lagoon fishing pressure is close to the optimum values noted during the study period. An ARIMA forecasting model indicates that the fishing yield will decline and at low levels for the next five years period (2015–2019). Thereafter, we assume that time series landing data and the ecological indices could be proposed, under certain preconditions, as a supplementary tool for the typing transitional water bodies, in the context of the European Water Frame Directive (WFD), and for future coastal management decisions.